ENHANCING STUDENTS’ ORAL ARTICULATION IN ENGLISH BY USING GAMIFICATION: STUDENTS’ PERCEPTION - Ridhon, Muti’an; Daulay, Sholihatul Hamidah (Universitas Cokroaminoto Palopo, 2023)
Gamification offers various types of learning English, especially oral articulation. Oral articulation or pronunciation is often a big problem in learning English, Therefore the students must be able to speak up with good articulation like a native speaker. One type of gamification is ELSA Speak Application. The study aims to know students’ articulation and students perception of learning English articulation by gamification. This application is used to train students’ oral articulation to match the articulation of native speakers. This study uses qualitative description and the data is taken through observation and interviews. The participant consisted of 20 students in the 9th grade of Junior High School in Medan. Based on the results of the interview, the students admitted that gamification can improve articulation in English. In conclusion, the students have positive experiences in learning English pronunciation or articulation by using gamification. They agree that learning with gamification makes it interesting and fun.